A high-performance structure for the bulk acoustic wave metal oxide semiconductor gas sensor. (29th August 2019) - Luo, Zhao; Tang, Qiang; Su, Songfei; Hu, Junhui
Abstract: It is known that bulk acoustic wave (BAW) can increase the sensitivity of a metal oxide semiconductor gas sensor and decrease its lower detection limit by at least one order of magnitude. However, the structure of BAW metal oxide semiconductor gas sensors has been bulky and its energy efficiency has been low. In this work, a new structure to form BAW metal oxide semiconductor gas sensors is proposed and investigated. In the structure, the metal case which is usually used to protect the sensing resistor, is employed to excite the working ultrasonic-field. A piezoelectric ring is bonded onto the bottom of the metal case to serve as the vibration excitation source of the whole system. The structure not only makes the gas sensor system compact and miniaturized by reducing the volume and weight of vibration excitation unit by more than 99%, but also decreases power consumption of the ultrasonic transducer by more than 98% for the same ultrasonic effect. Meanwhile the ultrasonic system can enhance the sensing response of a commercialized SnO2 gas sensor by one order of magnitude.